Islamic Finance in Finland - Sanaa Kadi (European Journal of Islamic Finance, 2023)
Abstract— This is a research based on the results of a survey conducted with Muslims residing in Finland about the reasons for not taking usurious loans and their reluctance to pay interest, which affects significantly the Muslim community and leads to their financial exclusion, such as preventing them from owning a dwelling in Finland or investing their money in projects that are in compliance with their religion.